2011
DOI: 10.1016/j.tcs.2010.08.025
|View full text |Cite
|
Sign up to set email alerts
|

P systems with minimal insertion and deletion

Abstract: In this paper we consider insertion-deletion P systems with priority of deletion over the insertion. We show that such systems with one symbol context-free insertion and deletion rules are able to generate P sRE. If one-symbol one-sided context is added to insertion or deletion rules but no priority is considered, then all recursively enumerable languages can be generated. The same result holds if a deletion of two symbols is permitted. We also show that the priority relation is very important and in its absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…Using even only the operations of minimal left insertion and minimal right deletion, matrix grammars reach computational completeness with matrices of length at most 3; our conjecture is that this required length cannot be reduced to 2. As our main result, we have shown that sequential P systems using the operations of minimal left and right insertion and deletion are computationally complete, thus solving an open problem from [2]. The simple P system constructed in the proof of Theorem 5 had rather large tree height; it remains an open question to reduce this complexity parameter.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Using even only the operations of minimal left insertion and minimal right deletion, matrix grammars reach computational completeness with matrices of length at most 3; our conjecture is that this required length cannot be reduced to 2. As our main result, we have shown that sequential P systems using the operations of minimal left and right insertion and deletion are computationally complete, thus solving an open problem from [2]. The simple P system constructed in the proof of Theorem 5 had rather large tree height; it remains an open question to reduce this complexity parameter.…”
Section: Resultsmentioning
confidence: 88%
“…When one of these parameters is decreased, this result is not true anymore [32]; moreover, even the graph-controlled variant cannot achieve computational completeness [19]. This changes when a graph control with appearance checking is used [1] or in the case of a random context control [16]. In both variants, minimal operations (involving only one symbol) were considered, leading to RE (the family of recursivey enumerable languages) in the case of setcontrolled random context conditions and to P sRE (the family of Parikh sets of RE) in the case of graph control with appearance checking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) q have been inserted into the string before and after some pairsXX, the rule q.3 will erase an instance ofX; the normalization condition will assure that the erased symbol was located exactly after $ (1) q . The contexts of the rule q.4 guarantee that the proper instance ofX has already been erased (the permitting condition $ (1) qX ) and will block the rule in the cases when $ (1) q is inserted betweenX andX and when $ (2) q is inserted after $ (1) q ; in the latter case q.3 would be blocked. The rule q.5 assures the proper localization of $ (3) q , i.e., before $ (1) q .…”
Section: It Can Be Seen That Ifmentioning
confidence: 99%
“…Insertion-deletion systems that are context-free [27], that have one sidedcontext [28] [23], and that are graph controlled [6] were also proposed. P -systems with insertion-deletion rules have been extensively studied in [22] [24] [2] [1] [7] [8]. A type of substitution operation inspired by errors occurring in biologically encoded information was proposed in [16].…”
Section: Introductionmentioning
confidence: 99%